Fracture resistance and fractographic analysis of pressable glass-ceramics with different partial coverage designs for maxillary premolars - Abdelaziz M. Abdelaal; Hany A. Kehela; Ahmed A. Holiel (BMC, 2024)
Abstract Background Partial coverage concepts have met the main goal of conservative dentistry. Vonlays, which combine features of veneers and onlays, are a recent alternative to full coverage designs and overlay partial coverage restorations. This in vitro study was conducted to compare the fracture resistance of the newly introduced pressable zirconia-reinforced lithium silicate with pressable lithium disilicate ceramic and to determine the optimal preparation design for partial coverage on upper premolars. Methods Fifty-two duplicated epoxy resin dies were prepared following vonlay and overlay preparation guidelines. For each preparation (n = 26), the specimens were divided into two subgroups to be restored with lithium disilicate (IPS e.max Press) or zirconia-reinforced lithium silicate (Vita Ambria) (n = 13 each). Ceramic vonlays and overlays were bonded using dual cure resin cement, subjected to thermomechanical fatigue, and the load to fracture was tested by using a universal testing machine. The specimens were fractographically analyzed via scanning electron microscopy (SEM). The normality of the fracture resistance data was checked using the Shapiro‒Wilk test and Q‒Q plots, and two-way ANOVA was used to assess the effect of the type of preparation and ceramic material on the fracture resistance. Results The group of overlays restored with zirconia-reinforced lithium silicate showed the highest mean fracture load (1218.69 N), while the group of vonlays restored with lithium disilicate had the lowest mean fracture resistance (967.15 N). The effect of preparation design and material type on fracture resistance was significant for both factors, p = 0.003 and p < 0.0001, respectively. Different features of the fracture surfaces, such as arrest lines, hackles, and directions of crack propagation, were observed. Conclusions Zirconia-reinforced lithium silicate exhibited greater resistance to fracture compared to lithium disilicate, making it a potential substitute for partial coverage restorations. Additionally, the overlay showed superior fracture resistance when compared to the vonlay preparation design.